MENELUSURI PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA TERHADAP KINERJA ANALIS KREDIT MIKRO PADA LEMBAGA KREDIT MIKRO PERBANKAN MAUPUN LEMBAGA KEUANGAN MIKRO - Wahyudiono, Bambang (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
Abstract:Credit quality and Non performing loan emerged during credit periode depend on credit analyst workindicator. Other factors are any activities done after drawdown bank loan to small and micro entriprizesas well. This research will explore non performing loan based on credit analyst performance. Analystperformance will be depend variable and professional competence and motivation will be independentvariables. Based on regression and correlation analysis, the result of the analysis show that Sig on theAnova tabels show Sig = 0.033 or less than probability value 0,05. The consecuenties Ho is refused anHa accepted. This mean that professional competence and motivation significantly and simultaneouslyinfluences performance. The regression line equation is -122,685 â 0,122x1 + 0,749x2. Determinantcoefisien or R = 0.5322. That is mean 53,2% analyst performance contributed by professionalperformance and motivation. Proporsion 46,8% will be determined by other unidentified factors.Keywords: Professional competence, Motivation, Credit analyst performance, Regression, Correlation,Credit analyst, Credit committee, Marketing Staf, Salses, Micro Credit.